Comparative evaluation of the diagnostic performance of four serological assays for bovine brucellosis in African buffalo (Syncerus caffer) - Michel, Anita Luise (University of Pretoria, 2016)
Mini-dissertation (MSc)--University of Pretoria, 2015.